Improving Patient Experience with Spinal Cord Stimulation: Implications of Position‐Related Changes in Neurostimulation. (2nd December 2011) - Ross, Edgar; Abejón, David
Abstract : Objectives: The objective of this narrative review is to discuss the clinical implications of position‐related changes in spinal cord stimulation and technological improvements to better meet patient needs. Methods: Keywords applicable to spinal cord stimulation therapy, including paresthesia perception, spinal cord position, lead impedance, and sensor technologies, were searched in the PubMed, EMBASE, and Cochrane Library databases. Literature analysis, combined with extensive clinical experience with spinal cord stimulation therapy, forms the basis of this review. Results: Fluctuations in paresthesia perception are largely caused by variation in the distance between the fixed electrodes and the spinal cord consequent to patient movement. Patients employ multiple strategies with varying success to manage position‐related fluctuations in stimulation perception, which may result in suboptimum therapy delivery. Conclusions: A new type of spinal cord stimulation system that incorporates accelerometer technology to automatically adjust stimulation amplitude based on patient position may better meet patient analgesic needs and is in early clinical application.